High performance liquid chromatographic method for the determination of guaifenesin in pharmaceutical syrups and in environmental samples (Baghdad Science Journal, 2025)
A simple, precise, rapid, and accurate reversed – phase high performance liquid chromatographic method has been developed for the determination of guaifenesin in pure from pharmaceutical formulations.andindustrial effluent. Chromatography was carried out on supelco L7 reversed- phase column (25cm × 4.6mm), 5 microns, using a mixture of methanol –acetonitrile-water: (80: 10 :10 v/v/v) as a mobile phase at a flow rate of 1.0 ml.min-1. Detection was performed at 254nm at ambient temperature. The retention time for guaifenesin was found 2.4 minutes. The calibration curve was linear (r= 0.9998) over a concentration range from 0.08 to 0.8mg/ml. Limit of detection (LOD) and limit of quantification ( LOQ) were found 6µg/ml and 18µg/ml respectively. The method was validated for its linearity, precision and accuracy .The proposed method was successfully applied for the determination of guaifenesin in syrups and industrial effluent samples.